2002
DOI: 10.1063/1.1464221
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a gamma-ray source based on a laser-plasma accelerator with applications to radiography

Abstract: The application of high intensity laser-produced gamma rays is discussed with regard to picosecond resolution deep-penetration radiography. The spectrum and angular distribution of these gamma rays is measured using an array of thermoluminescent detectors for both an underdense (gas) target and an overdense (solid) target. It is found that the use of an underdense target in a laser plasma accelerator configuration produces a much more intense and directional source. The peak dose is also increased significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(70 citation statements)
references
References 9 publications
0
68
0
1
Order By: Relevance
“…Other authors have previously conducted studies to characterise x-ray emission from high-power laser solid interactions across a variety of laser systems [24,25], as well as radiography demonstration of the imaging qualities of the beams [26,27,28]. In the present experiment the x-ray beam demonstrated large divergence which permits a large field of view, thus providing a suitable foundation for the development of tomographic imaging of large objects.…”
Section: Advantages Of a Laser Driven Sourcementioning
confidence: 73%
“…Other authors have previously conducted studies to characterise x-ray emission from high-power laser solid interactions across a variety of laser systems [24,25], as well as radiography demonstration of the imaging qualities of the beams [26,27,28]. In the present experiment the x-ray beam demonstrated large divergence which permits a large field of view, thus providing a suitable foundation for the development of tomographic imaging of large objects.…”
Section: Advantages Of a Laser Driven Sourcementioning
confidence: 73%
“…Because of the use of the extreme accelerating fields available in plasmas, typically of the order of TV/m, this approach has the potential to transform the technology of particle acceleration. Furthermore, it has been shown that the high-quality, low-emittance particle beams already produced in these experiments can today be utilized for measurements of ultra-rapid phenomena in physics, chemistry or for the production of gamma ray beams which have extremely small source sizes [57,58]. This work is leading to the production of high rep rate, sub-10 fsec, high quality electron beams in the GeV range.…”
Section: Discussionmentioning
confidence: 98%
“…Figure 1 shows that the γ-rays in the MeV energy region can be effectively generated by the radiation effect. It is well known that the γ rays can be generated by the bremsstrahlung with electrons generated by laser-plasmas [29]. If an electron beam with well-tuned continuous energies will be generated, its bremsstrahlung γ-rays may have quasi-stellar energy distribution as shown in Figure 2. …”
Section: Direct Measurement Of Stellar Nuclear Reaction Rate On the Gmentioning
confidence: 99%